Purification and characterization of cellulase from a novel isolate of Trichoderma longibrachiatum. Issue 1 (2nd January 2020) - Pachauri, Priyanka; V., Aranganathan; More, Sunil; Sullia, S. B.; Deshmukh, Sudha
ABSTRACT: In the present study, the isolation, purification and characterization of a complex enzyme, cellulase, was carried out using a new local isolate of the fungus Trichoderma longibrachiatum (KM274866) from wood chips, with a view to explore its utility in the biofuel industry. The fungus was grown on a selected natural substrate, sugarcane bagasse, based on cost considerations for enzyme production. The enzyme was purified 14.82 fold with a yield of 25.8% and specific activity of 30 U/mg of protein. The molecular mass of the enzyme was found to be 67 ± 1 KDa. The optimum pH was 4.8, but the enzyme was stable at a pH range of 3–6. Optimum temperature was 45 °C, but the stability range of the enzyme was 30–55 °C. Metal ions such as Ca 2+, Na +, Mg 2+, Zn 2+ and Fe 2+ enhanced enzyme activity. Triton X100 in the medium resulted in a significant increase of enzyme activity compared to other group specific reagents. KM and Vmax for the enzyme were found to be 0.121 mg/ml and 0.421 μmol/min, respectively, against the substrate carboxy methyl cellulose. As the enzyme is from an inexpensive source, it will be most useful in the preparation of bioethanol for the biofuel industry.